Managing Cisco network security - Knipp, Eric.; Danielyan, Edgar (Rockland, MA : Syngress, 2002)
An in-depth knowledge of how to configure Cisco IP network security is a MUST for anyone working in today's internetworked world "There's no question that attacks on enterprise networks are increasing in frequency and sophistication ..."--Mike Fuhrman, Cisco Systems Manager, Security Consulting Managing Cisco Network Security, Second Edition offers updated and revised information covering many of Cisco's security products that provide protection from threats, detection of network security incidents, measurement of vulnerability and policy compliance and management of security policy across an extended organization. These are the tools that network administrators have to mount defenses against threats. Chapters also cover the improved functionality and ease of the Cisco Secure Policy Manger software used by thousands of small-to-midsized businesses and a special section on the Cisco Aironet Wireless Security Solutions. Security from a real-world perspective Key coverage of the new technologies offered by the Cisco including: 500 series of Cisco PIX Firewall, Cisco Intrusion Detection System, and the Cisco Secure Scanner Revised edition of a text popular with CCIP (Cisco Certified Internetwork Professional) students Expanded to include separate chapters on each of the security products offered by Cisco Systems.
Includes index.
First edition published as: Managing Cisco network security : building rock-solid networks. Rockland, MA : Syngress, c2000.
Keywords: Cisco Systems, Inc; Computer networks -- Security measures; Computer networks -- Management; Electronic books